Diskon Angka Kembar: Trik atau Ilusi Bisnis? Kajian Sosiologi Ekonomi Islam terhadap Perlindungan Konsumen - Adawiah, Amalia Muazzah; Abdal, Abdal; Arifin, Tajul (Jurnal Hukum Ekonomi Syariah : AICONOMIA, 2024)
The phenomenon of twin-digit discounts in digital transactions is increasingly popular and raises various questions regarding consumer protection from the perspective of Islamic economic sociology. These discounts are often used as a marketing strategy, but concerns also arise regarding their long-term impact on consumer welfare, particularly in terms of transaction fairness and transparency. This study aims to examine how consumer protection is applied in digital transactions involving twin-digit discounts and how the principles of Islamic economic sociology can offer solutions to these challenges. Using a descriptive qualitative method, data was collected through literature review and analysis of phenomena in society. The findings emphasize the importance of stronger regulation and consumer awareness in identifying potential risks that may arise from these discount practices.